2022
DOI: 10.3390/jcm11175220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preceding Transcranial Direct Current Stimulation on Movement Velocity and EMG Signal during the Back Squat Exercise

Abstract: This study aimed to evaluate the effects of preceding anodal transcranial direct stimulation (a-tDCS) over the dorsolateral prefrontal cortex (DLPFC) during the back squat exercise on movement velocity and surface electromyographic (sEMG) activity. Thirteen healthy, well-trained, male firefighters (34.72 ± 3.33 years; 178 ± 7.61 cm; 76.85 ± 11.21 kg; 26.8 ± 4.2 kg·m−2; back squat 1-repetition maximum 141.5 ± 16.3 kg) completed this randomised double-blinded sham-controlled crossover study. After familiarisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…One reason might be the fact that in the present study we did not use transcranial magnetic stimulation (TMS) which is the most standard method for hot spotting the precise region representing the motor area of the lower limb over the M1 for tDCS (17). It is worth mentioning that, however, the international 10-20 EEG system has been corroborated as a valid method for stimulating target areas in the brain in most of the previous studies (9,15,20,21,43). In addition, the demanding nature of the hypoxic condition might have had a regulatory role in the M1 response to the anodal tDCS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One reason might be the fact that in the present study we did not use transcranial magnetic stimulation (TMS) which is the most standard method for hot spotting the precise region representing the motor area of the lower limb over the M1 for tDCS (17). It is worth mentioning that, however, the international 10-20 EEG system has been corroborated as a valid method for stimulating target areas in the brain in most of the previous studies (9,15,20,21,43). In addition, the demanding nature of the hypoxic condition might have had a regulatory role in the M1 response to the anodal tDCS.…”
Section: Discussionmentioning
confidence: 89%
“…The causative effect of tDCS on the muscle EMG has been a controversial topic as most of the studies did not see any effect of tDCS on the muscle EMG (6, 41, 42) while some recent ndings suggest that tDCS might affect the muscle EMG (7,21,38,43). In this sense, changes in the motor unit recruitment strategies as a result of brain stimulation have been suggested as the mechanism by which tDCS could induce its effect on muscle activity re ected by EMG (7,38).…”
Section: Discussionmentioning
confidence: 99%
“…The causative effect of tDCS on muscle EMG has been a contentious topic because most studies found no effect of tDCS on muscle EMG [ 6 , 44 , 45 ]. While some recent findings suggest that tDCS may affect muscle EMG [ 7 , 21 , 39 , 46 ]. Changes in motor unit recruitment strategies as a result of brain stimulation have been proposed as a mechanism by which tDCS could induce its effect on muscle activity as reflected by EMG [ 7 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that we did not use transcranial magnetic stimulation (TMS) to precisely target the region representing the motor area of the lower limb in M1 [ 17 ]. However, in most previous studies, the international 10–20 EEG system has been confirmed as a valid method for stimulating target areas in the brain [ 9 , 15 , 20 , 21 , 46 ]. In addition, the montage used in the present study has previously been tested and shown to increase corticospinal excitability and endurance performance [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the same protocol was carried out in the exercises leg extension, lat pull down and lying femoral, in that order in all sessions. Finally, we proceeded to perform three sets of 12 repetitions in squat using a linear encoder with 70% of the 1-RM based on [ 18 ], to assess velocity loss and perceived effort. At the end of the sessions, all the participants reported their perception of the training session on a scale of one to ten.…”
Section: Methodsmentioning
confidence: 99%